Bardet‐Biedl syndrome: Weight patterns and genetics in a rare obesity syndrome - Pomeroy, Jeremy (Pediatr Obes, 2020)
BACKGROUND: Bardet‐Biedl syndrome (BBS) is a rare genetic disorder that severely inhibits primary cilia function. BBS is typified by obesity in adulthood, but pediatric weight patterns, and thus optimal periods of intervention, are poorly understood. OBJECTIVES: To examine body mass differences by age, gender, and genotype in children and adolescents with BBS. METHODS: We utilized the largest international registry of BBS phenotypes. Anthropometric and genetic data were obtained from medical records or participant/family interviews. Participants were stratified by age and sex categories. Genotype and obesity phenotype were investigated in a subset of participants with available data. RESULTS: Height and weight measurements were available for 552 unique individuals with BBS. The majority of birth weights were in the normal range, but rates of overweight or obesity rapidly increased in early childhood, exceeding 90% after age 5. Weight z‐scores in groups >2 years were above 2.0, while height z‐scores approached 1.0, but were close to 0.0 in adolescents. Relative to those with the BBS10 genotype, the BBS1 cohort had a lower BMI z‐score in the 2‐5 and 6‐11 age groups, with similar BMI z‐scores thereafter. Children with biallelic loss of function (LOF) genetic variants had significantly higher BMI z‐scores compared to missense variants. CONCLUSION: Despite normal birth weight, most individuals with BBS experience rapid weight gain in early childhood, with high rates of overweight/obesity sustained through adolescence. Children with LOF variants are disproportionally affected. Our findings support the need for earlier recognition and initiation of weight management therapies in BBS.